The ‘Cultural Notions’: A Proposal for a Methodological Shift in the Teaching of Spanish as a Foreign Language - Artero Abellán, Pablo Agustín (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The 2018 Instituto Cervantes’ yearbook called it first: Spanish is on the rise (Fernández, 2018). Prospectively yet, Spanish health will rely on many factors beyond the coincidental: innovative teachers, better resources and original methodologies. Spanish students have, for years, studied English as a Foreign Language by the hand of the “four skills”, where arbitrary topics were piled up around so-called ‘units’. This has been a by-product of the influence that publishing houses such as Cambridge have had in Spain. The following pages, however, bring forth an alternative rejuvenating model: a new teaching scheme based on the French educational model known as ‘cultural notions’.